2023
DOI: 10.3390/polym15030782
|View full text |Cite
|
Sign up to set email alerts
|

Coating Materials to Increase the Stability of Liposomes

Abstract: Liposomes carry various compounds with applications in pharmaceutical, food, and cosmetic fields, and the administration route is especially parenteral, oral, or transdermal. Liposomes are used to preserve and release the internal components, thus maintaining the properties of the compounds, the stability and shelf life of the encapsulated products, and their functional benefits. The main problem in obtaining liposomes at the industrial level is their low stability due to fragile phospholipid membranes. To inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 193 publications
(153 reference statements)
0
13
0
Order By: Relevance
“…Based on current knowledge, the use of biopolymer complexes rather than individual biopolymers appears to be more promising for regulating stability and creating 'smart', stimulusresponsive liposomal forms of nutraceuticals. 12,20,21 For instance, the whey protein-chitosan (CHIT) complexes that contained PC liposomes loaded with polyphenols (such as green tea extract or curcumin) demonstrated superior storage stability when compared to control liposomes. These complexes were able to resist changes in their particle size and ζ-potential, 22 as well as curcumin degradation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on current knowledge, the use of biopolymer complexes rather than individual biopolymers appears to be more promising for regulating stability and creating 'smart', stimulusresponsive liposomal forms of nutraceuticals. 12,20,21 For instance, the whey protein-chitosan (CHIT) complexes that contained PC liposomes loaded with polyphenols (such as green tea extract or curcumin) demonstrated superior storage stability when compared to control liposomes. These complexes were able to resist changes in their particle size and ζ-potential, 22 as well as curcumin degradation.…”
Section: Introductionmentioning
confidence: 99%
“…27 However, the role of chitosan in the digestion and absorption of liposomes remains controversial. 12,20 Moreover, there is still incomplete comprehension regarding the behaviour and absorption mechanisms of biopolymercoated liposomal forms of nutraceuticals within the digestive tract. 12,20 Thus, the main objective of this study was to gain an indepth understanding of the key structural factors and intermolecular interactions that underlie the formation, functionality and behaviour in the gastrointestinal tract (GIT) in vitro of the biopolymer-coated liposomal delivery system for a combination of hydrophobic and hydrophilic nutraceuticals, [WPI-(PC-FO-D3-GABA-CEO)]-CHIT.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, a common problem for liposomal drugs is physical instability and the loose coordination of liposomal structures. The fluidity of the phospholipid bilayer causes the frequent intramolecular contact of QT, and long-term storage can lead to drug leakage and formation of QT crystals. The pharmaceutical stability of liposomes can be improved by the surface coating using amphipathic polymers such as DSPE-PEG, Pluronic L61, and Tween 80. There is still a continuous need to search for efficient means to prolong the liposomal shelf life . Recently, it was found that the β-CD and its derivatives could interact with the headgroup of phospholipids, coat on the membrane surface, and coordinatively increase the liposomal stability .…”
Section: Introductionmentioning
confidence: 99%